Teacher Competence and Religious Character on Learning Achievement: The Mediating Role of Islamic Extracurriculars - Pratiwi, Nanda; Soraya, Siti Zazak; Daryono, Rihab Wit (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This study aims to analyze the influence of teacher competence and religious character on the learning outcomes of students' moral creed in MAN 1 Trenggalek. A quantitative approach is used with the survey method, which is conducted retrospectively to examine the variable construction of learning outcomes of moral creed students. This research design uses explanatory and correlational approaches with Partial Least Squares Structural Equation Modeling (PLS-SEM) as an analytical tool. This study involved 98 MAN 1 Trenggalek students as samples, selected using purposive sampling techniques. Data were collected through questionnaires with four variables: Teacher Competence (X1), Religious Character (X2), Islamic Extracurricular as a mediator (Z), and Learning Achievement in Islamic Education (Y). Data collection is done through Google Forms. Data analysis using PLS-SEM, with testing stages of measurement and structural models. Measurement model testing aims to validate and estimate the reliability of indicators and constructs. The results show that all indicators meet the requirements of validity and reliability. Structural model evaluation aims to assess model predictions against empirical data and the predictive power of the model. The results show that teacher competence and religious character significantly impact the learning outcomes of students' moral creeds. Religious extracurriculars mediate the relationship between teacher competence and moral creed learning outcomes. This study concludes that teacher competence and religious character contribute significantly to the learning outcomes of students' moral creeds. This research contributes to the development of educational theory by highlighting the relationship between teacher competence, religious character, and student learning achievement, as well as the mediating role of Islamic extracurricular activities. This research concludes that teacher competence and student religious character have a positive influence on student learning achievement.